Analisis Sistem Manajemen Kinerja terhadap Kinerja Karyawan Caddy Golf - Putri Mustika Anggraeny; Suryari Purnama (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
In an era of increasingly intense business competition, an organization's success heavily depends on the quality of individual performance within it. Achieving optimal performance becomes key in realizing organizational goals. In the golf industry, the role of service staff, particularly caddies, is vital as the frontline service that directly interacts with customers. This ongoing research aims to analyze the influence of performance management systems on employee performance of golf caddies at Senayan golf Club. Using a quantitative approach, this research involved 167 respondents and employed multiple regression analysis. The research results show that goal setting, performance feedback, performance assessment, and rewards have a significant positive effect on employee performance, while training has a positive but low significant effect. Meanwhile, the simultaneous influence of independent variables positively affects employee performance. The implications of this research demonstrate the importance of developing a comprehensive performance management system focusing on goal setting, feedback, performance assessment, training, and effective reward systems